2013
DOI: 10.2478/jas-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Polish Unifloral Honeys IV. Honeydew Honey, Mainly Abies Alba L.

Abstract: S u m m a r yConiferous honeydew honey, mainly Abies alba was characterised. Samples chosen for the study had organoleptic traits characteristic for the variety: greenish, opalescence tone of brown colour, mild, sweet flavour with pleasant, slightly resinous aftertaste and aroma as well as electrical conductivity over 0.95 mS/cm. To define composition and physicochemical parameters of the variety, contents of water and total sugars were determined. In addition various carbohydrates were identified and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 9 publications
10
29
2
Order By: Relevance
“…Comparing the results obtained in this study with the results for European unifloral honeys reported by the International Honey Commission (Persano Oddo & Piro, 2004), our results for black locust honey were slightly lower than for the European black locust honey samples (112 -337 mg/kg). The proline content of other honey types analysed in this study was in compliance with our previously reported results for sage and honeydew honey (Kenjerić et al, 2006;Primorac et al, 2009) as well as with the proline content of the same honey type from different geographical regions (Cavrar et al, 2013;Rybak-Chmielewska et al, 2013). The enzymes in honey mainly originate from the bee, but the enzyme activities of different honey types varies according to botanical origin.…”
Section: Discussionsupporting
confidence: 76%
“…Comparing the results obtained in this study with the results for European unifloral honeys reported by the International Honey Commission (Persano Oddo & Piro, 2004), our results for black locust honey were slightly lower than for the European black locust honey samples (112 -337 mg/kg). The proline content of other honey types analysed in this study was in compliance with our previously reported results for sage and honeydew honey (Kenjerić et al, 2006;Primorac et al, 2009) as well as with the proline content of the same honey type from different geographical regions (Cavrar et al, 2013;Rybak-Chmielewska et al, 2013). The enzymes in honey mainly originate from the bee, but the enzyme activities of different honey types varies according to botanical origin.…”
Section: Discussionsupporting
confidence: 76%
“…These results indicated that the honey was fresh. The range of diastase activity was similar to that found in other honeydew honeys (Persano-Oddo & Piro, 2004;Primorac et al, 2009;Rybak-Chmielewska, Szczę sna, Waś, Jaśkiewicz, & Teper, 2013) but higher than the values reported by Díez et al (2004) and Bentabol et al (2011).…”
Section: Physicochemical Characterisationsupporting
confidence: 85%
“…The pH value of the honeys ranged from 3.65 to 4.53. These values were similar to those obtained by other authors (2,6,14,26,31,42,43,48,51,52).…”
Section: Resultssupporting
confidence: 82%
“…to 42.3% (on average 37.7%) (39,40). The protein content in honey is in the range of 500-10 000 mg/kg (on average 2000 mg/kg) (41), and mineral content ranges from 500 to 3500 mg/kg (8,25).…”
mentioning
confidence: 99%